2013
DOI: 10.1016/j.ydbio.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Activation and function of TGFβ signalling during Drosophila wing development and its interactions with the BMP pathway

Abstract: The development of the Drosophila wing disc requires the activities of the BMP and TGFβ signalling pathways. BMP signalling is critical for the correct growth and patterning of the disc, whereas the related TGFβ pathway is mostly required for growth. The BMP and TGFβ pathways share a common co-receptor (Punt) and a nuclear effector (Medea), and consequently it is likely that these pathways can interfere with each other during normal development. In this work we focus on the spatial activation domains and requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 42 publications
3
59
0
Order By: Relevance
“…The size defects observed upon loss of Smad2 are not caused by gross defects in cell growth or viability, or by defects in any particular cell cycle transition, but they can be mostly attributed to a decrease in cell proliferation rates (Hevia and de Celis 2013). We examined the proliferation of Smad F4 mutant cells by clonal analysis in Smad2 F4 FRT19A/ FRT19A Ubi-GFP hs-FLP1.22 wing discs and found that Smad2 homozygous mutant clones are smaller than their wild-type twins (Figure 1,M and N).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The size defects observed upon loss of Smad2 are not caused by gross defects in cell growth or viability, or by defects in any particular cell cycle transition, but they can be mostly attributed to a decrease in cell proliferation rates (Hevia and de Celis 2013). We examined the proliferation of Smad F4 mutant cells by clonal analysis in Smad2 F4 FRT19A/ FRT19A Ubi-GFP hs-FLP1.22 wing discs and found that Smad2 homozygous mutant clones are smaller than their wild-type twins (Figure 1,M and N).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that changes in the function of Smad2 do not cause specific defects in either the G1 to S or G2 to M cell cycle transitions (Hevia and de Celis 2013), suggesting that both steps might be affected to a similar extent. We examined the expression of two cell cycle regulators, CycE and string, in loss-of-function Smad2 wing discs.…”
Section: Smad2 Combinations With Cell Cycle Regulatorsmentioning
confidence: 98%
See 1 more Smart Citation
“…To identify ligands that may be redundant for Gb'dpp, RNAi was used to target various Gryllus homologs of the Drosophila TGF-β family members (21), including Gb'gbb, activinß (Gb'actβ), maverick (Gb'mav), and myoglianin (Gb'myo).…”
Section: Resultsmentioning
confidence: 99%
“…We wondered whether this simultaneous low phototaxis and the absence of wing-clipping effect was due to a specific effect of these mutations or a general consequence of both manipulations altering the flies' wing utility. To tackle this question, we tested three lines with flight impairments, the flightless PKC d mutant, the wings of which are indistinguishable from wild-type wings (figure 2d), the CyO balancer line with curly wings, and a transgenic line in which the wings were deformed due to an overexpression of a constitutively active form of the baboon receptor in wing imaginal discs (A9.babo QD [36]). …”
Section: Discussionmentioning
confidence: 99%